Sensory processing in autism spectrum disorders and Fragile X syndrome—From the clinic to animal models. (May 2017) - Sinclair, D.; Oranje, B.; Razak, K.A.; Siegel, S.J.; Schmid, S.
Highlights: Sensory information needs to be filtered pre-attentively for the brain to function properly. Autism spectrum disorder (ASD) and Fragile-X syndrome (FXS) are associated with hyper- and hyposensitivity indicating sensory filtering disruptions. Different event-related potentials and behavioral measures can be used in humans and animal models to assess sensory filtering. We here review evidence from clinical population and relevant animal models showing that sensory filtering disruptions are a robust feature of ASD and FXS. Abstract: Brains are constantly flooded with sensory information that needs to be filtered at the pre-attentional level and integrated into endogenous activity in order to allow for detection of salient information and an appropriate behavioral response. People with Autism Spectrum Disorder (ASD) or Fragile X Syndrome (FXS) are often over- or under-reactive to stimulation, leading to a wide range of behavioral symptoms. This altered sensitivity may be caused by disrupted sensory processing, signal integration and/or gating, and is often being neglected. Here, we review translational experimental approaches that are used to investigate sensory processing in humans with ASD and FXS, and in relevant rodent models. This includes electroencephalographic measurement of event related potentials, neural oscillations and mismatch negativity, as well as habituation and pre-pulse inhibition of startle. We outline robust evidence of disrupted sensory processing in individuals with ASD and FXS, and in respective animal models, focusing on the auditory sensory domain. Animal models provide an excellent opportunity to examine common mechanisms of sensory pathophysiology in order to develop therapeutics.